Community Wellbeing Under China-Pakistan Economic Corridor: Role of Social, Economic, Cultural, and Educational Factors in Improving Residents’ Quality of Life - Aman, Jaffar; Abbas, Jaffar; Shi, Guoqing; Ain, Noor Ul; Gu, Likun (Frontiers in Psychology, 2022)
This present article explores the effects of cultural value, economic prosperity, and community mental wellbeing through multi-sectoral infrastructure growth projects under the Belt and Road Initiative. The implications of the social exchange theory are applied to observe the support of the local community for the China-Pakistan Economic Corridor (CPEC). This study explores the CPEC initiative, it’s direct social, cultural, economic development, and risk of environmental factors that affect residents’ lives and the local community’s wellbeing. CPEC is a multibillion-dollar project to uplift economic growth and free trade between Pakistan, China, and other regional stakeholders. Although CPEC is still in its initial phases with partial startups, policymakers and government officials claim this mega project as a “game-changer” in the region, mainly for Pakistan and China. This gigantic project offers the significant potential to generate business slews and employment opportunities with international outreach. Due to the term’s newness, numerous studies have recently explored the macro and microeconomic benefits of the CPEC initiatives; still, these projects are theoretical. The existing literature insufficiently explored how helpful CPEC would be to a specific group and how residents perceive its advantages. This study fills in the literature gaps and explores the likely advantageous potential of the CPEC for the regional states. The study applied a convenient sampling technique for the data collection process. It used a mixed-method approach to gain scientific results, with a standardized questionnaire survey of 459 people (300 men and 159 women) from five major cities of Pakistan. The study results designate that residents believe that CPEC infrastructure projects will significantly improve residents’ life quality through more job openings and community poverty reduction. Still, they raised their concerns regarding environmental protection issues in the region. The findings specified that residents had an optimistic approach to better educational productivity by adopting environment-oriented policies. Policymakers should establish new CPEC study centers in different areas, and investors should be encouraged to participate in the industrial sector. Officials can overwhelm community worries about environmental degradation. Government officials in both countries can utilize the findings to raise public awareness about CPEC’s social, economic, cultural, mental wellbeing, and ecological implications.